Association of Growth Hormone (GH) Gene Diversity with Quantitative Characteristics in KUB Chicken Using PCR-RFLP Method - Sidik, Wahid Hasyim; Depison, Depison; Gushariyanto, Gushariyanto (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
The length of the title is recommended to not exceed fifteen words. This study aimed to obtain GH gene diversity and GH gene association. The materials used were 96 KUB chickens and 96 blood samples of 43 males and 53 females. The research method was experimental. The data collected included body weight, weight gain, and body size of male and female KUB chickens as well as the diversity of GH genes and the association of GH genes: T-test, principal component analysis (MCA), T2-Hotelling test, genotype frequency, alleles, Hardy-Weinberg equilibrium, heterozygosity and polymorphic information content (PIC). The results showed that body weight at 2 and 3 months of age, body weight gain at 2 to 3 months, and body size of male KUB chickens at 3 months of age were significantly different (p<0.05) higher than female KUB chickens. Body weight, body weight gain, and body size of male KUB chickens were higher than female KUB chickens. Body size characteristics of male and female KUB chickens were chest circumference, and male body shape characteristics were breast length and upper body length in females. The GH|MspI gene of KUB chickens is polymorphic and has associations with body weight, weight gain and body size with the best genotype being +/+.